2012
DOI: 10.1016/j.jcrs.2012.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Impact of corneal aberrations on through-focus image quality of presbyopia-correcting intraocular lenses using an adaptive optics bench system

Abstract: The uncorrected corneal astigmatism and HOAs in pseudophakic eyes significantly affected through-focus performance of presbyopia-correcting IOLs. Although multifocal IOLs significantly increased depth of focus, this benefit diminished when more than 0.75 D astigmatism remained uncorrected. Residual ocular spherical aberration had a significant effect on image quality in the presence of other corneal HOAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 31 publications
1
32
0
1
Order By: Relevance
“…However, problems such as glare and halo due to multifocal IOLs implanted in the patients with preexisting corneal astigmatism have been frequently encountered in the studies. [7][8][9] Several methods, including changing the site of incision in phacoemulsification, astigmatic keratotomy or limbal relaxation incisions, have been tried during surgery to reduce astigmatism. However, these procedures have restrictions such as long-term mechanical instability and the limited degree of astigmatism that can be corrected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, problems such as glare and halo due to multifocal IOLs implanted in the patients with preexisting corneal astigmatism have been frequently encountered in the studies. [7][8][9] Several methods, including changing the site of incision in phacoemulsification, astigmatic keratotomy or limbal relaxation incisions, have been tried during surgery to reduce astigmatism. However, these procedures have restrictions such as long-term mechanical instability and the limited degree of astigmatism that can be corrected.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] However, it was reported that depth of focus reduces and problems such as blurred vision, photophobia, halo and glare are more prevalent in the patients that underwent multifocal IOL implantation and have uncorrected corneal astigmatism of 0.75 diopter and over. [7][8][9] In addition to correction of refractive defect and enabling near vision without the need for eyeglasses, also correction of astigmatism has been possible with multifocal toric IOL that has been manufactured recently. Accordingly, dependency on eyeglasses following surgery has become less prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Such lenses will be developed with the basic aim of allowing patients to achieve both close and distance vision without a requirement for corrective glasses (1) these lenses reduce internal aberrations and compensate for corneal astigmatism and aberrations, these benefits are minimized in the context of an uncorrected astigmatism exceeding 0.75 diopters (D). In addition, image quality is significantly affected in the presence of other higher-order corneal aberrations (HOCAs) (2) . The associated surgical procedure remains the primary cause of induced corneal changes, especially astigmatism and aberrations (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Equipped with a corrector such as a deformable mirror, an adaptive optics system is able to separate or combine different aberrations including an SA with a continuous amplitude. 11,12 Adaptive optics has been used to simulate the aberrations of an IOL, 13 test IOLs with produced aberrations, 14 and subjectively evaluate IOLs free from implantation. 15 Given their sophisticated diffractive structure and foldable material, such as acrylic, whether a batch of DIOLs has similar optical quality remains a question.…”
Section: Introductionmentioning
confidence: 99%